Marett og mana - Tybjerg, Tove (Religionsvidenskabeligt tidsskrift, 2018)
Robert Ranulph Marett's (1866-1943) name is closely identified with the mana-concept. In some influential essays around 1900 and in critical dialogue with Tylor and Frazer, Marett proposed to use mana' as a technical term. Many were persuaded by Marett's argument, but used the mana-concept in such a broad and heterogenous way, that it was soon deemed unfit for scientific use. As a result of Marett being more or less forgotten afterwards, few have been aware, that Marett's arguments are more sophisticated than is usually acknowledged. Danish historians of religion have taken a more vivid interest in mana and the mana-concept; on a different basis, some of the issues - discussed in Denmark in connection with the mana-concept - are now under debate in New animism'.